The use of virtual tours for cognitive preparation of visitors : a case study for VHE - Widyarto, Setyawan; Abd. Latiff, Muhammad Shafie (Emerald Group Publishing Limited, 2007)

(untitled)
Purpose – The purpose of this paper is to explore the issue of using virtual tours to improve health and safety through preparatory familiarisation for visits to the swarming area. The main objective of the virtual environment system is path finding by commanding spatial skills. Design/methodology/approach – Provides a case study of the area of Jamarat. One of the main ritual sites during the Hajj, in which Muslims stone the devil during the annual pilgrimage, will be unveiled from a virtual reality perspective and visual analytics. Findings – The virtual environment built may help people interested in a virtual tour of the environment but have no opportunity to go due to limitations or may facilitate participants in pre-departure preparation of a dangerous environment. Practical implications – This paper's main issue is using virtual environments for virtual tours and discusses the principles of virtual environment creation and information extraction from available sources using a case study. Originality/value – The development of the case study environment will be used for training purposes of the Hajj pilgrim candidates to avoid any possible fatal distraction.